2007
DOI: 10.1007/s10665-007-9195-x
|View full text |Cite
|
Sign up to set email alerts
|

A brief historical perspective of the Wiener–Hopf technique

Abstract: It is a little over 75 years since two of the most important mathematicians of the 20th century collaborated on finding the exact solution of a particular equation with semi-infinite convolution type integral operator. The elegance and analytical sophistication of the method, now called the Wiener-Hopf technique, impress all who use it. Its applicability to almost all branches of engineering, mathematical physics and applied mathematics is borne out by the many thousands of papers published on the subject sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 53 publications
0
104
0
Order By: Relevance
“…The general question of constructive matrix Wiener-Hopf factorisation is open: (Lawrie & Abrahams 2007;Rogosin & Mishuris 2016). In this paper we are concerned with a class of Wiener-Hopf equations with triangular matrix functions containing exponential factors.…”
Section: Introductionmentioning
confidence: 99%
“…The general question of constructive matrix Wiener-Hopf factorisation is open: (Lawrie & Abrahams 2007;Rogosin & Mishuris 2016). In this paper we are concerned with a class of Wiener-Hopf equations with triangular matrix functions containing exponential factors.…”
Section: Introductionmentioning
confidence: 99%
“…For geometries comprising semi-infinite duct sections the Wiener-Hopf technique [15] can prove to be a powerful tool. The method is most appropriate for the solution of 2-D (or 3-D) boundary value problems involving a governing equation together with a two-part boundary condition imposed along one infinite coordinate line [16,4] (for example, one condition for x < 0, y = 0 and a different condition for x > 0, y = 0).…”
Section: Introductionmentioning
confidence: 99%
“…Mixed BVPs (where the boundary conditions change on part of the boundary) cannot be solved in general by the classic transform method. Nevertheless, for some of these problems it is possible, after using a suitable transform, to express their solution in terms of a Wiener-Hopf (or Riemann-Hilbert) problem [83], [70]. The application of the new method to these types of problems is work in progress; preliminary investigations have shown that the global relation yields immediately the relevant Wiener-Hopf problem, thus eliminating the need to first choose a suitable transform.…”
Section: Extensions Of the Method And Connections With Other Techniqmentioning
confidence: 99%